2011
DOI: 10.1186/cc10462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes in arterial pressure on organ perfusion during septic shock

Abstract: IntroductionSeptic shock is characterized by altered tissue perfusion associated with persistent arterial hypotension. Vasopressor therapy is generally required to restore organ perfusion but the optimal mean arterial pressure (MAP) that should be targeted is uncertain. The aim of this study was to assess the effects of increasing MAP using norepinephrine (NE) on hemodynamic and metabolic variables and on microvascular reactivity in patients with septic shock.MethodsThis was a single center, prospective, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(120 citation statements)
references
References 26 publications
9
105
0
6
Order By: Relevance
“…A recent research also demonstrated that a history of hypertension serves as a protective factor for liver-associated clinical decompensation and mortality (7). Another study also showed that a lower MAP of 50-60 mmHg has a positive correlation with a higher morbidity in case of kidney dysfunction (8).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…A recent research also demonstrated that a history of hypertension serves as a protective factor for liver-associated clinical decompensation and mortality (7). Another study also showed that a lower MAP of 50-60 mmHg has a positive correlation with a higher morbidity in case of kidney dysfunction (8).…”
Section: Introductionmentioning
confidence: 86%
“…MAP is regarded as perfusion pressure of the organs required to maintain blood flow and is considered as the most important hemodynamic parameter for the function of the circulation system. MAP is the determinant factor for maintaining cerebral and renal blood flow (6,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Badin and colleagues [10] have reported that acute kidney injury is decreased with a MAP of at least 72 mmHg. However, which MAP levels should be targeted to improve microcirculation remains controversial [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Avant l'intervention, la sévérité des anomalies était très variable d'un individu à l'autre. De plus, chez certains patients, ils ont observé une amélioration du pourcentage de petits vaisseaux perfusés et chez d'autres une franche aggravation [45]. Le groupe de Ince a confirmé ces résultats sur un groupe plus important de patients [46].…”
Section: Hémodynamique Globale Et Microcirculationunclassified